DAMPAK RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS BURSA EFEK INDONESIA (BEI) DENGAN MODERASI GOOD CORPORATE GOVERNANCE (GCG) - Nuranggeraeni, Dina; Anas, Dimas Emha Amir Fikri; Irianto, Mochamad Fariz (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2025)
This study aims to examine the effect of financial performance on financial distress by considering the role of Good Corporate Governance (GCG) as a moderating variable. The research focuses on retail companies listed on the Indonesia Stock Exchange (IDX) during the 20192023 period, a sector that has experienced significant financial pressure in recent years due to rising interest rates and intense competition. Financial performance is measured through leverage ratio, activity, operational cash flow, and profitability, which are commonly used indicators to evaluate the stability of a companys financial condition. To predict financial distress, this study applies the Altman Z-Score and the Springate Model, both recognized for their reliability in bankruptcy prediction. Data analysis uses a quantitative approach with the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The population consists of 23 companies, with 19 companies selected as samples through purposive sampling, resulting in 95 observations. The findings reveal that leverage, activity, cash flow, and profitability significantly affect financial distress, while the moderating role of GCG shows mixed results depending on the financial ratio tested. This research contributes to both theory and practice by providing insights into early identification of financial risks and offering recommendations for companies to strengthen governance mechanisms as part of their mitigation strategies.